Significados atribuídos ao sofrimento psíquico por parte de profissionais emergencistas - Oliveira, Hilda Coutinho de (2010)
Research about the feelings on psychological suffering, their configuration and coping strategies with twelve professionals in a hospital emergency in the city of Fortaleza (Ceará). It was used a qualitative method, participant observation and semi-structured interview. Researched group formed by four doctors, four nurses and four nursing auxiliaries. It was considered behavioral and verbal expressions of the subjects that worked in different hospital sectors. It was possible to highlight recurrent issues under pluralistic material, and to decipher their meanings. The study of mental suffering was done according to chosen categories. The contents of the described categories have been comprehended on a Psychoanalytical basis and, more specifically, on the ideas of Dejours concerning the psychodynamics of work. The findings of the present research are not suitable for generalizations. They were described in the paper´s final considerations. The following results were achieved: work in emergency meant altruism and learning; it was noticed that there was precariousness of material and human resources, and psychophysical risks under the conditions of work; challenges, rituals, subordination and conflicts were present in the field of working organization; the mental suffering appeared as the conflict between the omnipotence and vulnerability by workers; the coping strategies covered physical and emotional disorders, the defenses were found to be in the field of denial, identification, illusion of an existing group, as well as of the family, leisure and religion.